2005
DOI: 10.3988/jcn.2005.1.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Blepharospasm and Apraxia of Eyelid Opening in Patients with Parkinsonism

Abstract: Background and PurposeBlepharospasm (BSP) and apraxia of eyelid opening (AEO) have been reported as dystonia related with parkinsonism. However, systematic analysis of clinical characteristics of BSP and AEO in parkinsonism has been seldom reported. To investigate the clinical characteristics of BSP and AEO in parkinsonism and to find out the clinical significance to differentiate parkinsonism.MethodsWe enrolled 35 patients who had BSP with or without AEO out of 1113 patients with parkinsonism (913 IPD, idiopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
3
33
2
Order By: Relevance
“…In our study, the frequency of BSP was increased in patients with atypical parkinsonism, for example in PSP (10.52%) versus in IPD (3.26%). In contrast to the findings of Yoon et al [2], our findings did not indicate the presence of BSP among MSA patients, possibly due to the small number of MSA and also CBD patients in our study. We also prospectively followed 10 patients with BSP and of those, only 2 developed IPD.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In our study, the frequency of BSP was increased in patients with atypical parkinsonism, for example in PSP (10.52%) versus in IPD (3.26%). In contrast to the findings of Yoon et al [2], our findings did not indicate the presence of BSP among MSA patients, possibly due to the small number of MSA and also CBD patients in our study. We also prospectively followed 10 patients with BSP and of those, only 2 developed IPD.…”
Section: Discussioncontrasting
confidence: 56%
“…There have been many reports that indicate that BSP is much more prevalent in IPD, atypical parkinsonism [2] and other movement disorders including CD [1,8]. Different studies have examined this relationship but the results have not unequivocally indicated an association between BSP and parkinsonism or CD.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations